Ecoenzymes as Environmentally Friendly Detergents: Economic Empowerment Innovation - Mahdian Mahdian; Parham Saadi; Rizal Iskandar; Husnul Khatimah; Alvince Stevani Lase (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
The underutilization of pineapple peel waste and fluctuations in pineapple prices are among the challenges faced by Tinggiran Darat Village. The objective of this Community Empowerment Partnership (PKM) initiative is to empower pineapple farmers by transforming pineapple peel waste into economically valuable products, namely eco-enzymes and liquid laundry detergent. To address these issues, the program adopts an Asset-Based Community Development (ABCD) approach, involving 40 members of the PKK/ Pemberdayaan Kesejahteraan Keluarga (Family Welfare Movement) and youth organizations. The evaluation results through pretest and posttest showed a significant increase in all indicators of participant understanding, namely from 52.25 to 87.5 on the eco-enzyme concept, from 50.0 to 86.75 on the production process, from 48.0 to 89.0 on environmentally friendly detergent products, and from 60.0 to 87.5 on digital marketing and branding aspects, all of which were in the very good category. In addition, the results of the public perception analysis showed a positive level of acceptance of eco-enzyme-based detergent products, with 84.4% of respondents rating the product's cleaning power as good, 90.6% stating it was safe for the skin, 78.1% rating the packaging as quite attractive, and 81.3% stating a willingness to reuse and recommend the product. As an explicit impact, the community is now able to independently process previously discarded pineapple peels into marketable natural detergent products. This has proven effective in reducing the village's organic waste volume while simultaneously creating new, sustainable economic income opportunities for the local community.